Perancangan Sistem Informasi Perpustakaan Berbasis Desktop Pada SMA Negeri 1 Samalantan Kabupaten Bengkayang - Daniel Robi Sanjaya; Chandra Lesmana; Henny Puspitasari (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to find out how to design and build a library information system, determine the feasibility and user response after the desktop-based library information system was implemented at SMA Negeri 1 Samalantan, Bengkayang Regency. The research method used in this research is Research and Development. The research model used is ADDIE. The research was conducted by trial by media experts and practitioners as many as 4 people and 70 respondents, the research was conducted from May to June 2022. The results of this study are desktop applications in the form of splash display, apk initial display, login, registration, dashboard, student data, data teachers, book catalogues, borrowing, returns, reports, and developers. The design of this desktop - based library information system uses Java Netbeand software version 8.2 and Xampp version 8.1.2.